The Role of Quantified Parameters on River Plume Structure: Numerical Simulation - Jiaxin Zhang; Kan Hong; Yeping Yuan; Ying-Tien Lin; Dongrui Han (Journal of Marine Science and Engineering, 2024)
A three-dimensional numerical model was established with OpenFOAM-5.x to investigate plume characteristics under windless and rainless weather conditions. The large eddy simulation was applied, combined with a modified solver for solving governing equations with the Boussinesq approximation in a single rotating frame. The relationship between plume characteristics (e.g., gradient Richardson number and maximum plume width) and quantified parameters (e.g., rotation period, shelf slope, and reduced gravity) was analyzed progressively. The results show the model can reproduce the change in plume types and instability found in the laboratory experiments. With the increase in the rotation period, river plumes change from a surface-advected type to a bottom-attached type. The outline of the plume bulge accurately delineates the external region where the gradient Richardson number is less than 0.25, as well as the region near the wall. When the shelf slope approaches 0, the offshore movement becomes stronger while the alongshore coastal current comes into being with a delay associated with the slope and the rotation period. Compared with the extremely gentle slope case and the steep slope case, the maximum width in the gentle slope case changes significantly at about 1.5 rotation periods. Greater reduced gravity does promote offshore propagation, especially near the surface.